Uji Efek Anti Anafilaksis Kutan Aktif Dari Ekstrak Etanol Daun Ketepeng Cina (Cassia Alata L.) Pada Mencit Putih Jantan - Yufri Aldi; Yaser Arafat; Zet Rizal (STIFARM Padang, 2013)
An assay of the active cutaneous anti anaphylactic of the ethanolic extract of the Cassia alata L. On male white mice has been studied. The assay was done by giving three different doses (100,300, 900 mg per kg body weight ). Allergic reaction was induced by giving egg’s albumin as antigen. The anti anaphylactic effect was determined by measurement of the pro long of occurrence time, the dereased in diameter and the color intensity of the blue bump formed by using blue evan’s solution as indicator which was given intravenously. Result indicated the ethanolic extract of Cassia alata L. (100, 300, 900 mg per kg body weight ) had significant effect for each dose (p<0.05). The dose of 900 mg per kg body weight showed best effect.